Os Jazzes de Igarapé-Mirí : dimensões culturais do entretenimento musical moderno no Baixo Tocantins (1940-1970) - SINIMBÚ, Renato Pinheiro (Universidade Federal do Pará, 2019)
This dissertation sought to study the “Jazzes”, musical formations that existed in the municipality of Igarapé-Mirí between the 1940s and 1970s. These musical groups created for entertainment and dance were part of a broad cultural dialogue started in the United States and Central America from the 1920s on, directed by the music business. This was spread to other parts of the world. In Igarapé-Mirí, in particular, those groups were "embraced" by the elites, who used them for entertainment and to raise the economic level of their events and to embrace some festive spaces to these groups. On the other hand, the musicians, mostly black and poor, saw those formations as a way to become professional and acquire social prestige and thus try to break with economic problems and racial prejudices. The work tries to demonstrate how the Jazzes - corresponding to an innovative cultural dimension - were developed from traditional practices of musical production and enjoyment, disseminated from religious events of popular Catholicism and the festive dynamics diffused by the communities of the county. This study was carried out in large part through the production of interviews with the various dwellers of the Baixo Tocantins, based on the life history of a certain number of musicians in order to discuss the processes of musical formation, performance, agency, discrimination, resistance and subsistence. In this way, music was the means by which we sought to perceive the relations between the approached subjects.